SYNTACTIC STRUCTURES AND MEANING OF PREDICATE PREPOSITIONAL PHRASES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article investigates the syntactic configurations and semantic roles of predicate prepositional phrases (PPs) in English. It examines their structural integration within clauses, their functional roles, and the subtle interplay between form and meaning. Through theoretical frameworks and practical examples, we explore how these PPs contribute to predicate argument structure and semantic interpretation.